Evaluation of the Bioactivities of Rumex crispus L. Leaves and Root Extracts Using Toxicity, Antimicrobial, and Antiparasitic Assays - Idris, Oladayo Amed (Evid Based Complement Alternat Med, 2019)
Traditional folks in different parts of the world use Rumex crispus L. for the treatment of microbial infections, malaria, and sleeping sickness in the form of decoction or tincture. In the search for a natural alternative remedy, this study aimed to evaluate the antimicrobial, antitrypanosomal, and antiplasmodial efficacy and the toxicity of R. crispus extracts. Antimicrobial potency of the extracts was evaluated using the agar dilution method to determine the minimum inhibitory concentration (MIC). The antitrypanosomal activity of the extracts was evaluated with the Trypanosoma brucei brucei model while the antimalaria potency was tested using Plasmodium falciparum 3D7 strain. Toxicity was then tested with brine shrimp assay and cytotoxicity (HeLa cells). The acetone extract of the root (RT-ACE) reveals the highest antimicrobial potency with the lowest MIC value of <1.562 mg/mL for all bacteria strains and also showed high potent against fungi. RT-ACE (IC(50): 13 μg/mL) and methanol extract of the leaf (LF-MEE; IC(50): 15 μg/mL) show a strong inhibition of P. falciparum. The ethanol extract of the root (RT-ETE: IC(50): 9.7 μg/mL) reveals the highest inhibition of T.b. brucei parasite. RT-ETE and RT-ACE were found to have the highest toxicity in brine shrimp lethality assay (BSLA) and cytotoxicity which correlates in the two assays. This research revealed Rumex crispus has potency against microorganisms, Trypanosoma, and Plasmodium and could be a potential source for the treatment of these diseases.